Multisite collaboration using REDCap to capture library data - Grinstead, Carrie (J Med Libr Assoc, 2019)
In January 2018, library services at Providence St. Joseph Health merged to form a single, unified system, incorporating nine libraries and sixteen full-time staff. As a small, nonclinical team of librarians, we needed to make sure our work and value were visible to clinicians, administrators, and other nonlibrary stakeholders. Using REDCap, we developed a form to seamlessly collect statistics about our services.